M&As Efficiency Gains: Evidence from Branch-Level Data - Argentieri Mariani, Lucas; Ricca, Bernardo (Journal of Financial and Quantitative Analysis, 2026)
Abstract We examine how banks reallocate employees following mergers and acquisitions (M&As) and the resulting effects on productivity. Using matched employee–branch data combined with branch-level financial information, we show that M&As expand internal labor markets and trigger substantial worker redeployment. Newly consolidated banks reassign high-ability loan officers to acquirer branches, increasing productivity. Target branches also experience productivity improvements, primarily driven by restructuring and cost reductions. These effects are strongest in municipalities where the combined pre-merger internal labor markets of the target and acquirer were larger, highlighting the central role of internal labor markets in generating efficiency gains from consolidation.